Enhancing Teacher Performance: A Meta Analytic Examination of Organizational Citizenship Behavior and Proactive Personality - Achmad Ardiansyah; Widodo; Hendro Prasetyono (Jurnal Penelitian Pendidikan IPA, 2025)
Teacher performance is crucial for improving the quality of education in schools and the academic performance of students. Past studies have shown that both OCB and positive personality can have a significant impact on teacher performance. However, in order to better understand the strength and consistency of the correlation between these factors and performance, it is necessary to comprehensively integrate and analyze previous empirical findings. This meta-analysis examines the impact of organizational citizenship behavior (OCB) and proactive personality on teacher performance, synthesizing findings from 35 empirical studies published between 2020 and 2025. The results show that both OCB (r = 0.533) and proactive personality (r = 0.444) have significant positive effects on teacher performance, with OCB having a slightly stronger influence. The analysis reveals moderate heterogeneity across studies and no evidence of publication bias. These results strongly demonstrate the need for nuturing and it is OCB and proactive personality in schools to enhance teacher effectiveness. Practical implications include promoting a sense of organizational belonging and informal recognition to improve teacher performance outcomes.